Overimitation and faithful nonsense imitation of 4- to 7-year-old children: developmental changes vary with task type and demonstrated nonsense action - Pauen, Sabina; Bach, Jule (Social development, 2025)
Imitation plays a crucial role in early social learning. Numerous studies indicate that young children copy even actions that are clearly irrelevant for goal achievement—a phenomenon called overimitation (OI). The present study tested whether this finding can be generalized to different forms of faithful nonsense imitation presented in different task settings. To investigate this, N = 148 four- to seven-year-old children (primarily White, from families with a higher educational background, equally distributed across age) were asked to (1) retrieve a cookie from a transparent container, (2) color a picture with crayons, and (3) build a tower from packages of paper tissue. In a demonstration condition (n = 80), children watched the experimenter demonstrate goal-irrelevant actions (Container Task), counterintuitive color-choices (Picture Task), and goal-inconsistent behavior (Tower Task) before entering the test phase. In a baseline condition (n = 28), children only participated in the test phase and were instructed to accomplish each task as they liked. In an order control condition (n = 40), the task sequence was changed. Regardless of task order, task type, and gender, the predefined nonsense actions were performed more frequently in the demonstration than in the baseline condition for all three tasks. At the same time, standardized imitation scores and developmental pathways varied substantially between tasks. Based on these findings, we conclude that young children show a general tendency to faithfully imitate nonsense actions in rather different goal-directed tasks, but that task characteristics play a key role for predicting imitation performance.